Effectiveness of the Sowan Program Holistic Nursing Intervention on the Independence of Pulmonary TB Patients - Tamrin, Ike Nurjana; Asikin, Muhammad; Nuralamsyah, Muhammad (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Researchers analyzed the effect of the SOWAN program on the independence of TB patients physically, psychological management, socially and spiritually. Method: The design used was quasi-experimental with a quantitative approach. With 40 respondents who met the criteria selected as samples with 20 people in the intervention group and 20 others as controls. The intervention created was a health education package called SOWAN, an abbreviation of support, observation, welfare and action. Results: The results showed that there was an increase in the independence of respondents in the intervention group after using the SOWAN program (average before intervention 32.8667 and after intervention 55.33) and the difference value was significant p = 0.000. In addition, there was also a significant difference between the intervention group and the control group after the intervention became p 0.000. This is also seen from the use of the health card. The condition used by respondents in the intervention group after conducting the SOWAN program for 6 weeks increased from an average of 3 to 4.9 (range of values ​​1 - 5). Conclusion: this shows that the SOWAN program has proven to be effective in making TB clients independent in physical, psychological, social and spiritual independence. So this SOWAN program is recommended for use in Nursing with other chronic diseases through maternal and child health programs.